Effect of Sodium Bicarbonate Buccal Infiltration on the Success of Inferior Alveolar Nerve Block (IANB) in Mandibular First Molars with Symptomatic Irreversible Pulpitis - Abdullah; Sheikh, Abubakar; Islam, Shahid; Muhammad Ali; Beg, Zainab; Khan, Nasir (Indus Journal of Bioscience Research, 2025)
Background: The endodontic access of mandibular molars with symptomatic irreversible pulpitis requires achieving profound anesthesia which failure of inferior alveolar nerve block (IANB) frequently dictates the need to administer additional injections. Sodium bicarbonate Buffering/alkalinizing regimens (e.g. sodium bicarbonate) could be useful to enhance anesthetic performance in inflamed tissues. Objective: To determine the effect of sodium bicarbonate buccal infiltration on the success of IANB in mandibular first molars with symptomatic irreversible pulpitis. Methods: This comparative analytical (quasi-experimental) research was done in the Department of Operative Dentistry and Endodontics, Fatima Jinnah Dental College and Hospital, Karachi from October 2023 to April 2024. A consecutive sampling was carried out to recruit 72 patients with symptomatic irreversible pulpitis in first molars of the mandible who were divided into two groups (n=36). All the patients were provided with standard IANB. Group A also obtained sodium bicarbonate buccal infiltration whereas Group B obtained control buccal infiltration. The level of pain was measured by a 10-point VAS at access and pulp extirpation. Success of IANB was the completion of access/initial instrumentation with VAS 3 or less without the need of supplemental anesthesia. Results: IANB success was significantly higher in Group A than Group B (69.4% vs 38.9%, p=0.009). Group A reported lower pain during access (2.4±1.6 vs 3.6±1.8, p=0.004) and pulp extirpation (2.9±1.7 vs 4.1±1.9, p=0.006), faster onset of lip numbness (3.8±1.2 vs 4.6±1.4 minutes, p=0.011), and reduced need for supplemental anesthesia (30.6% vs 61.1%, p=0.009). Adverse events were infrequent and comparable. Conclusion: Sodium bicarbonate buccal infiltration significantly improves IANB success and reduces intra-operative pain and supplemental anesthesia requirement in mandibular first molars with symptomatic irreversible pulpitis.